2016
DOI: 10.1111/mec.13790
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal relationship between adult census size and genetic population size across a wide population size gradient

Abstract: Adult census population size (N) and effective number of breeders (Nb ) are highly relevant for designing effective conservation strategies. Both parameters are often challenging to quantify, however, making it of interest to determine whether one parameter can be generalized from the other. Yet, the spatiotemporal relationship between N and Nb has not been well characterized empirically in many taxa. We analysed this relationship for 5-7 consecutive years in twelve brook trout populations varying greatly in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(87 citation statements)
references
References 77 publications
1
85
1
Order By: Relevance
“…Previous studies have found that although these CR brook trout populations differ nearly 50-fold in census size N and 10-fold in effective number of breeders N b (Bernos and Fraser, 2016), there is no evidence for differences in (i) quantitative genetic variation and trait differentiation in relationship to population size, nor (ii) phenotypic plasticity in relationship to population size (Wood and Fraser, 2015; Wood et al ., 2015). Therefore, our study provides further evidence that population size may not be tightly related to the ability of a population to respond to environmental change, and that thermal tolerance, in particular (physiologically and behaviourally), may be highly conserved even in such a plastic species as S. fontinalis .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have found that although these CR brook trout populations differ nearly 50-fold in census size N and 10-fold in effective number of breeders N b (Bernos and Fraser, 2016), there is no evidence for differences in (i) quantitative genetic variation and trait differentiation in relationship to population size, nor (ii) phenotypic plasticity in relationship to population size (Wood and Fraser, 2015; Wood et al ., 2015). Therefore, our study provides further evidence that population size may not be tightly related to the ability of a population to respond to environmental change, and that thermal tolerance, in particular (physiologically and behaviourally), may be highly conserved even in such a plastic species as S. fontinalis .…”
Section: Discussionmentioning
confidence: 98%
“…Another expected outcome might be that hybridizing between populations above and below the minimal viable population threshold would benefit smaller populations disproportionally. In our hybridized crosses, one large population (FW, see above) was hybridized with two smaller populations (STBC, see above; WC: mean N b = 31.36 and mean N  = 783.09; Bernos and Fraser, 2016) with little effect on any thermal tolerance trait, whether measured by mean or variance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While genetic drift has not received much empirical support as an explanation for the species richness gradient, it could be more relevant for intraspecific diversity. As patch size or a species’ range size is correlated with population size (Bernos & Fraser, ; Currie et al, ), it is a reasonable assumption that species with small ranges have, on average, smaller population sizes. This would lead to increased levels of genetic drift and an increased possibility of inbreeding, and hence lower GenPerSpp.…”
Section: Review: Understanding the Latitudinal Gradient Of Biodiversimentioning
confidence: 99%
“…For this purpose, a field experiment was conducted in which the density of young‐of‐the‐year (YOY) brook trout ( Salvelinus fontinalis ) was manipulated in isolated sections of small streams of Cape Race, Newfoundland, Canada. Our experiment was replicated both spatially (three sites per population) and temporally (three consecutive years) across three neighbouring populations that are known to differ in life history and stream characteristics (Bernos & Fraser, ; Hutchings, ). In our streams, food abundance is low, predation is negligible and growth rate of brook trout decreases with increasing water temperature, whereas mortality is exacerbated in acidic conditions (Hutchings, ; Yates, ).…”
Section: Introductionmentioning
confidence: 99%